2015
DOI: 10.18632/oncotarget.5320
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular stomatitis virus expressing interferon-β is oncolytic and promotes antitumor immune responses in a syngeneic murine model of non-small cell lung cancer

Abstract: Vesicular stomatitis virus (VSV) is a potent oncolytic virus for many tumors. VSV that produces interferon-β (VSV-IFNβ) is now in early clinical testing for solid tumors. Here, the preclinical activity of VSV and VSV-IFNβ against non-small cell lung cancer (NSCLC) is reported. NSCLC cell lines were treated in vitro with VSV expressing green fluorescence protein (VSV-GFP) and VSV-IFNβ. VSV-GFP and VSV-IFNβ were active against NSCLC cells. JAK/STAT inhibition with ruxolitinib re-sensitized resistant H838 cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 40 publications
2
79
0
2
Order By: Relevance
“…Improved safety of rVSV-mIFN-β was also confirmed in this study [106]. Along similar lines, rVSV-IFN-β was shown to induce a systemic antitumor immune response, marked by increased CD8 + tumor-infiltrating lymphocytes (TILs) and decreased Tregs and mMDSCs, in both injected and non-injected tumors, in a model of non-small cell lung cancer [107]. Furthermore, there was evidence of the onset of a memory immune response shown via rechallenge experiments in the same study [107].…”
Section: Strategies To Boost the Immune-stimulating Potential Of Vsvsupporting
confidence: 69%
“…Improved safety of rVSV-mIFN-β was also confirmed in this study [106]. Along similar lines, rVSV-IFN-β was shown to induce a systemic antitumor immune response, marked by increased CD8 + tumor-infiltrating lymphocytes (TILs) and decreased Tregs and mMDSCs, in both injected and non-injected tumors, in a model of non-small cell lung cancer [107]. Furthermore, there was evidence of the onset of a memory immune response shown via rechallenge experiments in the same study [107].…”
Section: Strategies To Boost the Immune-stimulating Potential Of Vsvsupporting
confidence: 69%
“…Using VSVs encoding type I and type III IFNs Several recent pre-clinical studies have shown that VSVIFNb and VSV-IFNb-NIS (additionally expresses the NIS to track virus spread) are oncoselective and safe in a variety of tumour and animal models [24,[27][28][29][30][31]. Although mice and rats continue to serve as the most commonly used animal models for VSV-based OV therapy, a recent study evaluated the safety of intravenously administered VSV-IFNb-NIS in purpose-bred beagle dogs.…”
Section: Improving Oncoselectivity and Safetymentioning
confidence: 99%
“…Another common approach is to use VSV-encoding IFNb (VSV-IFNb), which oncoselectivity is based on virus-encoded IFNb expression that stimulates an innate immune response in normal cells but not in type I IFN defective cancer cells [22,23]. IFNb also stimulates tumour-specific immunity [24]. VSV-IFNb showed no signs of neurotoxicity at any time point in rhesus macaques when administered via intrahepatic injection [22].…”
Section: Introductionmentioning
confidence: 99%
“…[14] Moreover, Aguiar et al [16] showed that nivolumab (inhibited PD-1 and PD-L1) treatment had different bioavailability and outcomes in PD-L1 negative and positive cases. Furthermore, although Patel et al [17] investigated vesicular stomatitis virus (VSV), they also reported positive results related to anti-tumor effect and tumor immunity due to increased PD-L1 expression after the interferon-b treatment.…”
Section: Discussionmentioning
confidence: 99%